β-Caryophyllene Ameliorates MSU-Induced Gouty Arthritis and Inflammation Through Inhibiting NLRP3 and NF-κB Signal Pathway: In Silico and In Vivo - Li, Wan-Yang; Yang, Fan; Chen, Ji-Hua; Ren, Guo-Feng (Frontiers in Pharmacology, 2021)
Gouty arthritis serves as an acute reaction initiated by the deposition of monosodium urate (MSU) crystals around the joints. In this study, the anti-inflammatory effects of phytochemical β-caryophyllene on MSU crystal-induced acute gouty arthritis in vivo and in silico were explored. Through bioinformatics methods and molecular docking, screen the specific influence pathway of β-caryophyllene on gout. Certain methods including enzyme-linked immunosorbent assay, western blotting, and immunohistochemical staining were adopted to quantify. β-caryophyllene markedly reduced inflammation and function of ankle joints in MSU Crystals-induced gouty arthritis rats, while decreasing serum cytokine levels. Furthermore, it inhibited the expression of NLRP3, Caspase-1, ASC, TLR4, MyD88, p65, IL-1β in the synovial tissue, so as to reduce inflammation and protect ankle joints’ function. A new research approach in which β-caryophyllene treatment to acute attacks of gout is provided through our results.